A survey on curvatures of Hessian manifolds - Yilmaz, Wuenevver Yildirim; Bektas, Mehmet (Pergamon-Elsevier Science Ltd, 2008)
This paper deals with the relationship of curvatures between Hessian and Riemannian manifolds. By making use of the methods of Shima [Shima H. Hessian manifolds of constant Hessian sectional curvature. J Math Soc Jpn 1995;47(4):735-53] we investigate a new approach to the curvatures of a manifold. Finally, some results are mentioned in the concluding remarks. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Energy Particle Physics; Hyperbolic Geometry; Space-Forms; Constant; Topology; Universe